The application and research progress of anti-angiogenesis therapy in tumor immunotherapy - Tu, Jingyao; Liang, Hang; Li, Chunya; Huang, Yongbiao; Wang, Ziqi; Chen, Xinyi; Yuan, Xianglin (Frontiers in Immunology, 2023)
Tumor immunotherapy, as the focus of scientific research and clinical tumor treatment in recent years, has received extensive attention. Due to its remarkable curative effect and fewer side effects than traditional treatments, it has significant clinical benefits for the treatment of various advanced cancers and can improve cancer patient survival in the long term. Currently, most patients cannot benefit from immunotherapy, and some patients may experience tumor recurrence and drug resistance even if they achieve remission overcome. Numerous studies have shown that the abnormal angiogenesis state of tumors can lead to immunosuppressive tumor microenvironment, which affects the efficacy of immunotherapy. Actually, to improve the efficacy of immunotherapy, the application of anti-angiogenesis drugs to normalize abnormal tumor vessel has been widely confirmed in basic and clinical research. This review not only discusses the risk factors, mechanisms, and effects of abnormal and normalized tumor angiogenesis state on the immune environment, but summarizes the latest progress of immunotherapy combined with anti-angiogenic therapy. We hope this review provides an applied reference for anti-angiogenesis drugs and synergistic immunotherapy therapy.